Listening to urban kids : school reform and the teachers they want - Wilson, Bruce L. (SUNY series, restructuring and school change., 2001)
"According to the many student voices in this book, urban middle school students want teachers who "stay on them" to complete their work, maintain orderly classrooms, give them the extra help they need to succeed, explain their work clearly, draw on a variety of teaching strategies, and make their work relevant and meaningful. This book, rich in detail, brings these inner-city students' perspectives to life and issues a compelling call for urban school reform that actually touches students' daily lives."--Jacket